Global Distribution of Carbohydrate Utilization Potential in the Prokaryotic Tree of Life - López-Mondéjar, Rubén; Tláskal, Vojtěch; da Rocha, Ulisses Nunes; Baldrian, Petr (mSystems, 2022)
Microorganisms dominate all ecosystems on Earth and play a key role in the turnover of organic matter. By producing enzymes, they degrade complex carbohydrates, facilitating the recycling of nutrients and controlling the carbon cycle. Despite their importance, our knowledge regarding microbial carbohydrate utilization has been limited to genome-sequenced taxa and thus heavily biased to specific groups and environments. Here, we used the Genomes from Earth's Microbiomes (GEM) catalog to describe the carbohydrate utilization potential in >7000 bacterial and archaeal taxa originating from a range of terrestrial, marine and host-associated habitats. We show that the production of carbohydrate-active enzymes (CAZymes) is phylogenetically conserved and varies significantly among microbial phyla. High numbers of carbohydrate-active enzymes were recorded in phyla known for their versatile use of carbohydrates, such as Firmicutes, Fibrobacterota, and Armatimonadota, but also phyla without cultured representatives whose carbohydrate utilization potential was so far unknown, such as KSB1, Hydrogenedentota, Sumerlaeota, and UBP3. Carbohydrate utilization potential reflected the specificity of various habitats: the richest complements of CAZymes were observed in MAGs of plant microbiomes, indicating the structural complexity of plant biopolymers. IMPORTANCE This study expanded our knowledge of the phylogenetic distribution of carbohydrate-active enzymes across prokaryotic tree of life, including new phyla where the carbohydrate-active enzymes composition have not been described until now and demonstrated the potential for carbohydrate utilization of numerous yet uncultured phyla. Profiles of carbohydrate-active enzymes are largely habitat-specific and reflect local carbohydrate availability by selecting taxa with appropriate complements of these enzymes. This information should aid in the prediction of functions in microbiomes of known taxonomic composition and helps to identify key components of habitat-specific carbohydrate pools. In addition, these findings have a high relevance for the understanding of carbohydrate utilization and carbon cycling in the environment, the process that is closely link to the carbon storage potential of Earth habitats and the production of greenhouse gasses.
Keywords: mikrobiota; carbohydrate-active enzymes; Phylogeny; uhlík; phylogenetic conservation; earth microbiome; habitat specificity; Bacteria; sacharidy; Carbohydrates; natural ecosystems; Microbiota; fylogeneze; Carbon